75.3k views
4 votes
What is he solution to the equation below​

What is he solution to the equation below​-example-1
User Dagoof
by
5.1k points

1 Answer

2 votes

Answer: G

Explanation:


(7)/(8)(x-(1)/(2))=-(49)/(80)

To make it easier to solve, we can get rid of the fraction multiplying the parenthesis. To do this, we multiply by the reciprocal or the inverted fraction. Rather, if the fraction is 7/8, the reciprocal will be 8/7


(8)/(7)*(7)/(8)(x-(1)/(2))=-(49)/(80)*(8)/(7)

Note that 49 and 7 can be simplified.

49/7=7

7/7=1

80 and 8 can also be simplified.

80/8=10

8/8=1

Leaving our equation like;


x-(1)/(2)=-(7)/(10)

Add 1/2


x=-(7)/(10)+(1)/(2)

Combine like terms;


x=(-7*2+10*1)/(10*2)


x=(-14+10)/(20)


x=-(4)/(20)

Simplify.

4/4=1

20/4=5


x=-(1)/(5)

User MechanisM
by
4.8k points